PARP14 inhibits microglial activation via LPAR5 to promote post-stroke functional recovery. Issue 10 (3rd October 2021) - Tang, Ying; Liu, Jinchang; Wang, Yu; Yang, Li; Han, Bing; Zhang, Yuan; Bai, Ying; Shen, Ling; Li, Mingyue; Jiang, Teng; Ye, Qingqing; Yu, Xiaoyu; et al.
ABSTRACT: Stroke is a major public health problem leading to high rates of death and disability worldwide, but no effective pharmacological therapy is currently available except for the use of PLAT (plasminogen activator, tissue). Here we show that PARP14 (poly (ADP-ribose) polymerase family, member 14) level was significantly increased in the peri-infarct zone of photothrombotic stroke (PT) mice. Genetic knockdown and pharmacological inhibition of PARP14 aggravated functional impairment and increased infarct volume in PT mice, while overexpression of PARP14 displayed the opposite effects. Furthermore, PARP14 was abundant in microglia, and downregulation of PARP14 increased post-stroke microglial activation, whereas overexpression of PARP14 alleviated microglial activation, possibly through microglial macroautophagy/autophagy modulation. Mechanistically, overexpression of PARP14 suppressed Lpar5 (lysophosphatidic acid receptor 5) gene transcription to inhibit microglial activation post stroke. Taken together, PARP14 is a stroke-induced signal that restricts microglial activation and promotes functional recovery, and can serve as a novel target to develop new therapeutic agents for stroke. Moreover, these findings may be conducive to proper use of various PARP inhibitors. Abbreviations : 3-MA: 3-methyladenine; AIF1/Iba-1: allograft inflammatory factor 1; CNS: central nervous system; CQ: chloroquine; DAPI: 4ʹ, 6-diamidino-2-phenylindole; DMEM: Dulbecco's modified Eagle's medium; DMSO: dimethyl sulfoxide; ELISA: enzyme-linked immunosorbent assay; FBS: fetal bovine serum; GFAP: glial fibrillary acidic protein; IL1B/IL-1β: interleukin 1 beta; IL6/IL-6: interleukin 6; LPAR5: lysophosphatidic acid receptor 5; MAP1LC3B: microtubule-associated protein 1 light chain 3 beta; NOS2/iNOS: nitric oxide synthase 2, inducible; OGD: oxygen glucose deprivation; PAR: polymer of poly (ADP ribose); PARP: poly (ADP-ribose) polymerase family; PBS: phosphate-buffered saline; PLAT/tPA: plasminogen activator, tissue; PT: photothrombotic stroke; qPCR: quantitative polymerase chain reaction; Rap: rapamycin; RBFOX3/NeuN: RNA binding protein, fox-1 homolog (C. elegans) 3; SQSTM1: sequestosome 1; TNF/TNF-α: tumor necrosis factor